Kebudayaan dan Sinkretisme terhadap Pembentukan Ruang serta Bentuk Rumah Tradisonal Tolotang Kabupaten Sidrap - Aris Alimuddin (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Architecture as result of the culture refined creation has been avowed as one of culture form which accomplised as reflection from human life, from time to time.Architecture as subtance of culture like as one for leanguage form “non-verbal” human nuaced symbolic. purpose of this detailed examination si to find out as for as culture and sinkretism influence toward shape establish ment with tradisional Tolotang district .Sidrap house form. The sort of this researchis qualitative methode and discriitive character. Data removal methode with direct observation, deep interview, sketch and documentation. The object research is unit house hindu Towani Tolotang comunity house. Result of the object research is unit bugis house hindu Towani Tolotang community.Result of research is unit bugis house hindu towani tolotang comunity house.result of the resarch show any transformation accure in in house column part and 2 combination house as one meanwhile in space as simbolic split into front porch which divide between main house and addition house.Concluded that by culture and sinkretism in derection to hindu Towani Tolotang cause different effect especially on the shappe and it space